2019
DOI: 10.3390/cells9010063
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Induces Polyspermy in Sea Urchin Eggs through a Non-Cholinergic Pathway Modulating Actin Dynamics

Abstract: While alkaloids often exert unique pharmacological effects on animal cells, exposure of sea urchin eggs to nicotine causes polyspermy at fertilization in a dose-dependent manner. Here, we studied molecular mechanisms underlying the phenomenon. Although nicotine is an agonist of ionotropic acetylcholine receptors, we found that nicotine-induced polyspermy was neither mimicked by acetylcholine and carbachol nor inhibited by specific antagonists of nicotinic acetylcholine receptors. Unlike acetylcholine and carba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…b' Egg treated with 1-MA for 70 min experience a normal Ca 2+ response with a CF (arrow) which precedes the single Ca 2+ wave. c′ Two Ca 2+ waves (arrowheads) as a result of polyspermic fertilization in overripe eggs inseminated 6 h after hormonal treatment pathways but is mediated by changes in the egg cortical Factin meshwork and its altered polymerization dynamics [187].…”
Section: Contribution Of Actin Dynamics To Sperm and Egg Activationmentioning
confidence: 99%
“…b' Egg treated with 1-MA for 70 min experience a normal Ca 2+ response with a CF (arrow) which precedes the single Ca 2+ wave. c′ Two Ca 2+ waves (arrowheads) as a result of polyspermic fertilization in overripe eggs inseminated 6 h after hormonal treatment pathways but is mediated by changes in the egg cortical Factin meshwork and its altered polymerization dynamics [187].…”
Section: Contribution Of Actin Dynamics To Sperm and Egg Activationmentioning
confidence: 99%
“…In a series of previous studies on starfish and sea urchin eggs, we demonstrated that polyspermy is closely linked to an anomaly in the actin cytoskeleton of the egg cortex. Indeed, when the actin cytoskeleton was artificially altered through the use of actin-targeting toxins and chemicals, an actin-binding protein cofilin, anti-depactin antibody, nicotine, or even by “ageing”, the eggs showed a strong tendency of polyspermic fertilization [ 27 , 29 , 39 , 55 , 56 , 57 , 58 ]. At variance with these experimental conditions that caused cytoskeletal alterations, the pretreatment of P. lividus eggs with DTT or TCEP in our experimental condition did not induce discernable changes in the structure of the cortical actin cytoskeleton (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…This may be one of the reasons why the DTT- and TCEP-pretreated eggs were not prominently polyspermic ( Table 1 and Table 2 ). Nonetheless, it is possible that the concerted rearrangement of the actin cytoskeleton taking place in the fertilized eggs during egg activation [ 25 , 28 , 29 ] may not be influenced by the DTT pretreatment. In other words, the reducing agent may not have a profound effect on the actin filaments inside a quiescent egg, but it may still affect the mobilization kinetics in post-fertilization eggs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations